2020
DOI: 10.1113/jp278731
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a physiological role of pulmonary arterial baroreceptors in sympathetic neural activation in healthy humans

Abstract: Key points In an anaesthetised animal model, independent stimulation of baroreceptors in the pulmonary artery elicits reflex sympathoexcitation. In humans, pulmonary arterial pressure is positively related to basal muscle sympathetic nerve activity (MSNA) under conditions where elevated pulmonary pressure is evident (e.g. high altitude); however, a causal link is not established. Using a novel experimental approach, we demonstrate that reducing pulmonary arterial pressure lowers basal MSNA in healthy humans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Therefore, other factors may predispose individuals with CMS to cardiovascular disease. However, we cannot exclude the possibility that elevated sympathetic vasomotor outflow and/or arterial baroreflex dysfunction may develop in more severe CMS, with elevated pulmonary arterial pressure (Simpson et al, 2020), which may contribute to the greater cardiovascular disease risk reported in moderate and severe CMS.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, other factors may predispose individuals with CMS to cardiovascular disease. However, we cannot exclude the possibility that elevated sympathetic vasomotor outflow and/or arterial baroreflex dysfunction may develop in more severe CMS, with elevated pulmonary arterial pressure (Simpson et al, 2020), which may contribute to the greater cardiovascular disease risk reported in moderate and severe CMS.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, in normoxic anesthetised animals, isolated increases in PAP elicit increases in sympathetic outflow in a positive feedback manner, via stimulation of baroreceptors located in the extra pulmonary arteries (Moore et al., 2011). The potential sympathoexcitatory role of pulmonary arterial baroreceptors in humans at HA has since been investigated (Simpson et al., 2020). During inhalation of vasodilator nitric oxide, which selectively lowered PAP by 25%, a similar reduction in MSNA burst frequency was observed in lowlanders at 4383 m (exposure range 4–9 days).…”
Section: Mechanisms Involved In Neural Adjustments To Hamentioning
confidence: 99%
“…One hypothesis for these findings was the parallel stimulation of cardiopulmonary afferents that can elicit opposing effects on peripheral sympathetic outflow. Other work has postulated the existence of a positive feedback sympathetic reflex originating from pulmonary baroreceptors (Simpson et al 2020). To date, human work has relied on assessing reflex responses to a variety of cardiopulmonary stimuli with limited capacity to quantify afferent activity.…”
mentioning
confidence: 99%
“…Other work has postulated the existence of a positive feedback sympathetic reflex originating from pulmonary baroreceptors (Simpson et al . 2020). To date, human work has relied on assessing reflex responses to a variety of cardiopulmonary stimuli with limited capacity to quantify afferent activity.…”
mentioning
confidence: 99%